1998
DOI: 10.1038/bjc.1998.747
|View full text |Cite
|
Sign up to set email alerts
|

New antimetabolites in cancer chemotherapy and their clinical impact

Abstract: Summary It is almost 50 years since antimetabolites were first found to have clinical antitumour activity, with Farber's discovery that aminopterin could cause remission in acute leukaemia. In the following 10 years, methotrexate, 6-mercaptopurine and 5-fluorouracil (5-FU) found their way into clinical practice. Subsequently, cytosine arabinoside was found to have activity in acute leukaemia, but, until recently, other significant developments have involved optimizing the efficacy of existing antimetabolites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 45 publications
0
80
0
3
Order By: Relevance
“…To address this question, we devised a strategy to arrest cells in S phase, where Chk1 levels are high (51). HeLa cells were blocked in S phase by treating them with a low concentration of gemcitabine, a nucleoside analog that is incorporated by DNA polymerase into replicating DNA, blocking further chain elongation (55,56). Gemcitabine-treated HeLa cells accumulated in S phase ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To address this question, we devised a strategy to arrest cells in S phase, where Chk1 levels are high (51). HeLa cells were blocked in S phase by treating them with a low concentration of gemcitabine, a nucleoside analog that is incorporated by DNA polymerase into replicating DNA, blocking further chain elongation (55,56). Gemcitabine-treated HeLa cells accumulated in S phase ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Important anticancer agents, such as cytosine arabinoside (Ara-C), gemcitabine, capecitabine, decitabine and 5-aza-cytidine, are cytidine analogues [23]. Historically, nucleoside analogues were developed as cytotoxic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies showed that gemcitabine has activity against metastatic bladder cancer (Stadler et al, 1997) and gemcitabine combined with cisplatin is now the standard treatment for metastatic bladder cancer (von der Maase et al, 2000). Gemcitabine is also active against nonsmall-lung cancer (Schiller et al, 2002) and breast, ovarian and head and neck cancers (Possinger, 1995;Kaye, 1998).…”
Section: Nucleoside Analogs Currently Used In Cancer Chemotherapymentioning
confidence: 99%